Understanding SONET/SDH and ATM : - Kartalopoulos, Stamatios V. (IEEE Press, 1999)
Optical communications and fiber technology are fast becoming key solutions for the increasing bandwidth demands of the 21st century. This introductory text provides practicing engineers, managers, and students with a useful guide to the latest developments and future trends of three major technologies: SONET, SDH, and ATM, and a brief introduction to legacy TDM communications systems.